The Effect of Outside Leaders on the Performance of the Organization: An Experiment - Marcela Ibanez; Elke Schaffland (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
In order to deal with crises, organizations often bring expert leaders from outside. However, relying in an outside leader can result in decreased performance of the organization. In this paper, we use an experiment to investigate the role of identity and skills of the outside leader on the performance of the organization. Our results indicate that outside leaders are less committed than inside leaders and that group members cooperate less with an outsider than an inside leader.
Keywords: 330; Social Identity; Leadership; Public Good Game; Lab Experiment